Design and verification of a highly accurate in-situ hyperspectral radiometric measurement system (HyperNav) - Barnard, Andrew; Boss, Emmanuel; Haëntjens, Nils; Orrico, Cristina; Frouin, Robert; Tan, Jing; Klumpp, Justin; Dewey, Michael; Walter, David; Mazloff, Matthew; Chamberlain, Paul (Frontiers in Remote Sensing, 2024)
Hyperspectral optical observations of the Earth's surface oceans from space offer a means to improve our understanding of ocean biology and biogeochemistry. NASA's Plankton, Aerosol, Cloud, ocean Ecosystem (PACE) satellite mission, which includes a hyperspectral ocean color instrument (OCI), will provide radiometric observations of surface ocean with near continuous spectral resolution across the near UV to NIR range. Maintaining sufficient accuracy over the lifetime of satellite ocean color missions requires a robust program for system vicarious calibration (SVC) and product validation. The SVC process combines satellite sensor data with in-situ radiometric/optical measurements to remove potential biases due to the combined errors from both satellite radiometric sensor calibration and atmospheric correction. As such, high accuracy, high-spectral resolution in-situ radiometric measurements are required to provide a principal source of truth for the satellite-derived products. To meet the requirements, a novel in-situ radiometric system, called HyperNav, has been developed, rigorously characterized and field tested. Key attributes of HyperNav are dual upwelling radiance heads coupled to individual spectrometers, spectral resolution of ∼2.2 nm (full width, half-maximum) across 320-900 nm, integrated shutter systems for dark measurements, and integrated tilt and pressure sensors.The HyperNav operational modes include traditional profiling and surface modes, as well as integration with an autonomous profiling float for unattended deployment, offering a new capability for a network of autonomous platforms to support the long-term needs for hyperspectral ocean color remote sensing observations. This paper describes the HyperNav design, in-situ operational modes, and field verification results.